LncRNA SCAMP1 disrupts the balance between miR-26a-5p and ZEB2 to promote osteosarcoma cell viability and invasion - Li, Rong; Chen, Zhen; Zhou, Yubo; Maimaitirexiati, Gulikezi; Yan, Qi; Li, Yuting; Maimaitiyimin, Adilijiang; Zhou, Changhui; Ren, Jingqin; Liu, Chengqing; Mainike, Abasi; Zhou, Peng; et al. (Frontiers in Oncology, 2022)
Osteosarcoma often occurs in children and adolescents and affects their health. The survival rate of osteosarcoma patients is unsatisfactory due to the lack of early detection and metastasis development and drug resistance. Hence, dissection of molecular insight into osteosarcoma initiation and progression is pivotal to provide the new therapeutic strategy. In recent years, long noncoding RNAs (lncRNAs) have burst into stage in osteosarcoma development and malignant behaviors. LncRNA SCAMP1 has been discovered to play an essential role in carcinogenesis and progression. However, the mechanisms of lncRNA SCAMP1-involved tumorigenesis have not been reported in human osteosarcoma. In this study, we utilized multiple cellular biological approaches to determine the function of lncRNA SCAMP1 in osteosarcoma cells. Moreover, we performed several molecular biological approaches to define the mechanism by which lncRNA SCAMP1 regulated cell viability and invasion in osteosarcoma. We dissected that lncRNA SCAMP1 promoted progression of osteosarcoma via modulation of miR-26a-5p/ZEB2 axis. In conclusion, targeting lncRNA SCAMP1 and its downstream targets, miR-26a-5p and ZEB2, might be a useful approach for osteosarcoma therapy.